Nantgarw and Swansea Porcelains An Analytical Perspective - Edwards, Howell G.M (Springer International Publishing, 2018)
This book gives a detailed account of the holistic research carried out on the analytical data obtained historically on the products of the Nantgarw and Swansea porcelain manufactories which existed for a few years only during the second decade of the 19th Century. A background to the establishment of the two factories, which are linked through the persons of the enigmatic William Billingsley and his kiln manager, Samuel Walker, involves the sourcing of their raw materials and problems associated with the manufacture and distribution of the finished products. A description of the minerals and additives used in porcelain production is recounted to set the scene for the critical evaluation of the comprehensive analytical data which have been published on Nantgarw and Swansea porcelains. For the first time, the author has adopted a nondestructive technique, Raman spectroscopy, to interrogate perfect samples of Nantgarw and Swansea porcelain, as well as a selection of shards from an archaeological excavation carried out at a waste dump at the Nantgarw China Works site. Following these experiments, several questions relating to the porcelain bodies of Swansea and Nantgarw china can be answered and a protocol established for the preliminary evaluation of items of suspect attribution to confirm or not the correctness of their assignment to these Welsh porcelain factories. .